MAP Egypt - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
MAP Egypt is a monitoring tool that keeps track of agricultural development projects and the subnational socioeconomic context in Egypt. The ultimate goal of the tool is to improve agricultural project planning, coordination and effectiveness. Specifically, MAP Egypt helps the Government, development partners, researchers and other interested parties to gain a quick overview of the state of agriculture in Egypt at the aggregate and the project level. The tool has been developed for and with the Ministry of Agriculture and Land Reclamation (MoALR) by the International Food Policy Research Institute (IFPRI) as part of the “Evaluating Impact and Building Capacity” (EIBC) project, funded by United States Agency for International Development (USAID). In order to effectively allocate funds, build synergies and evaluate future proposals, users can visualize and monitor the status and progress of agricultural projects categorized by sector, location, donor or common objectives, as well as track projects’ key performance indicators. To contextualize projects and evaluate which governorates require further assistance, users can also quickly map, zoom and chart a wide range of socioeconomic indicators, at subnational levels, on food and nutrition security, poverty and development across Egypt, with a focus on Egypt’s Sustainable Development Strategy 2030 (SDS 2030 Pillars) the Sustainable Development Goals (SDGs), and Other Socioeconomic Indicators.